A construção e validação parcial do protocolo de avaliação terapêutico ocupacional da repercussão da alteração do ciclo vigília¬sono nas ocupações - CORRÊA, Clemici Lima (2023)
Changing the sleepwake cycle changes the physiology and reflecting personal habits in the physical, biological or psychological level. The nursing staff is one of the categories of workers who suffer from sleep deprivation in their routine work. Such a change in nurses may result in an occupational performance unsatisfactory and dangerous work, and harm not only the physical, social, mental and occupational these workers. the construction of evaluation instruments that can be the basis for the understanding of occupational imbalances arising from sleep deprivation, in order to build methods, techniques, future intervention instruments to assist in the pursuit of occupational balance of the subjects and attended subjects is essential. Thus, the objective of this research was to create and validate partially a protocol to assess the impact of the change in sleep wake cycle in occupations in health and wellness. For this we used a quantitative study, exploratory, where he built up an Occupational Therapy Assessment instrument About Sleep (ATOSS) which underwent a pilot study of nine people of different educational levels and six occupational therapists. Through the pilot study results, we carried out the necessary changes and the instrument was applied to the nursing staff of the Hospital Abelardo Santos. Qualitative analysis was performed using the data obtained from the systematization of data in Microsoft Office Excel program. As for the validation of ATOSS Protocol was evaluated the correlation between the areas of ATOSS questionnaire and quality of sleep, by the ShapiroWilk test, ANOVA, KruskalWallis, was previously fixed the significance level alpha = 0.05 for hypothesis rejection nullity. The study design was carried out in the SAM software and statistical tests were performed at BioEstat. Statistically the instrument did not have his complete partial validation, because it had flaws, but could be traced the main occupations affected by the change of the sleepwake cycle how to prepare the most affected activities were items participation in education, leisure and care the power and the participation the most marked items were participation in education, leisure, religious custom and use of transport means. In relation to the welfare and health the most frequent value was assigned note 8 in relation to health symptoms that had more records were fatigue, irritability, emotional instability, difficulty concentrating, loss in memory and mood changes. However, in a qualitative analysis of the study, it was possible to identify the most affected occupations, both in preparation and in participation and health, it was confirmed what other studies have brought in their results, that changes in sleepwake cycle and the double journey of work, can harm the health condition of these workers may be the cause or consequence of an occupational imbalance. Before this study, it was possible to understand how occupational therapy can significantly contribute to health and quality of life of workers to consider sleep as an occupation that may be a facilitator or barrier to other occupations.